Eficácia e segurança de tratamentos para pericoronarite em adultos: revisão sistemática de estudos clínicos randomizados - Schalch, Tânia Oppido (2020)
Pericoronitis is the term used to describe soft tissue inflammation around the dental crowns, usually noted in semi-erupted lower third molars, representing the main acute oral infection of young adults. Usually, patients report pain, malaise, difficulty swallowing, trismus, reflex pain in the ear and head, and the individual may also present edema in the face, purulent secretion, fever, halitosis, mucosal macerated and lymphadenopathy. In some cases, local infection may be spread, promoting systemic infectious processes. Despite the local and systemic damage that pericoronitis can generate, the available literature on this condition as well as its treatments are limited, which makes it challenging to develop evidence-based therapeutic guidelines for this pathology. Objective: this study aims to investigate the forms of treatment for pericoronitis, trying to identify the most effective and safe ones. Method: a systematic review was developed following the methodological recommendations of the Cochrane Manual for Systematic Reviews of Interventions and PRISMA guidelines. Extensive and sensitive search for randomized clinical studies on treatments for pericoronitis were conducted in the main databases (MEDLINE, EMBASE, CENTRAL, LILACS, BBO, ICTRP, ClinicalTrials.gov, WHO and OpenGrey). Results: 7 randomized clinical trials (359 participants) were included. Limitations in these studies such as small sample number, allocation concealment as well as wide confidence intervals, generated inaccuracy of results and very low certainty of evidence. Conclusion: the results and the low certainty of the evidence found are insufficient to infer about the efficacy and safety of the treatments analyzed for pericoronitis, and high-quality randomized clinical trials are needed to increase confidence in the estimated effects